Influence parental- and child-related factors on the acceptance of SARS-CoV-2 test methods in schools and daycare facilities - Loy, Johanna K.; Kimmig, Christian; Klos, Simon; Wunram, Heidrun Lioba; Langer, Thorsten; Breitinger, Eva; Bender, Stephan (Frontiers in Public Health, 2024)
Rapid testing for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infections was an essential step in reducing the spread of the virus and monitoring pandemic development. Most mandatory standard pandemic testing in Germany has been performed in schools and daycare facilities. We investigated the influence of behavioral and attitudinal characteristics of children and caregivers on their acceptance of (i) antigen-based nasal swab rapid and (ii) oral saliva-based pooled Polymerase Chain Reaction (PCR) tests. Conducted through a cross-sectional survey between November and December 2021, with 1962 caregivers and 581 children/adolescents participating, the study evaluated the acceptability of each testing method on a six-point scale. Participants scored one test method conducted on their child at one of six levels with 1 and 6 denoting “excellent” (1) and “inadequate” (6), respectively. We considered demographic variables, vaccination status, child mental health (measured by the SDQ-questionnaire), and facility type (kindergarten, primary school, secondary school) as covariates. Results reveal a preference for saliva-based PCR tests over nasal swabs by about one grade, particularly among parents of unvaccinated children, especially if their child expressed future vaccination reluctance. Testing acceptance was lower among children with mental health issues, primary school-aged, and those with less-educated parents. Perception of test accuracy and convenience influenced attitudes, favouring saliva-based PCR tests. Moreover, children with mental health issues felt less secure during testing. To our knowledge, this is the first study to investigate the influence of different testing methods on testing acceptance for SARS-CoV-2 in children and caregivers. Our study identifies predictors of lower acceptance of public health surveillance measures and enables the development of educational programs on testing and vaccination tailored to the needs of specific target groups. Moreover, we demonstrate that test acceptance in vulnerable groups can be enhanced by careful choice of an appropriate testing method.